STUDIES ON THE OCCURENCE AND GROWTH RATE OF TWO INTERTIDAL FOULING BRYOZOANS IN THE MATTANCHERRY CANNEL OF COCHIN HARBOUR, SOUTH- WEST COAST OF INDIA - NAIR, N UNNIKRISHNAN (Fishery Technology, 2025)
Occurrence and growth rates of two species of intertidal fouling bryozoans namely Electra bengalensis (Stoliczka) and Electra crustulanta (PaHas) are presented in this paper. The former was a typically marine form, settling on panels only during the high saline conditions of the premonsoon period and were absent during the low salinity conditions of the monsoon period, while the latter appeared to be a typical brackish water form settling on panels during the Jow saline conditions existing during the monsoon and postmonsoon periods and were totally absent during the premonsoon months. Regression co-efficient of the former was higher th m that of the latter suggesting more pronounced growth in Electra bengalensis. Maximum growth for this species was noticed during March, April and May (pre-monsoon) while for the other species growth was more or less similar during monsoon and postmonsoon months (June-January) showing that the species was at home in oHgohaHne and mesohaHne waters.